(untitled) (Linguostylistic Studies, 2020)
The article highlights the issue of identifying peasant names of the XVI-XVIII centuries on the territory of the Starostat Grabovetsky. The authors of the article focus on the analysis of the archival materials that have survived. Several basic norms that contribute to understanding of peasant names origin have been identified. The emphasis is on the phenomenon of bilingualism, which existed in that area and contributed greatly to this process. The study uses the original source records. The purpose of the article is to elucidate the ways/methods of identifying male names among the peasants, which were typical on the territory of Grabowski Starostat from the XVI to XVIII centuries. Anthroponymic material received from archival sources provides excellent opportunities for research. On the basis of source materials it is possible to define types of town personal names, allocate the means used for their creation, and also distinguish the anthroponyms, taking into account a social status of their carriers. In Starostat Grabovetsky, the monomial system of authentication prevailed among peasants at the earlier stages (to the middle of XVI cent.). Afterwards, with the necessity of extended authentication, patronymic name, which was evened by appellative, was added, very often naming geography of the person’s origin. There were also determinants that specified the status of the person by origin.